1959
DOI: 10.1002/j.2333-8504.1959.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of Personality: Cautiousness and Intolerance of Ambiguity1

Abstract: Objective personality tests were developed for two aspects of intolerance of ambiguity: (a) the tendency to reach perceptual closure quickly and (b) the tendency to jump to generalizations on the basis of specific information. The two tests utilized a tab format which enabled the subject either to respond immediately to an item or to request more information, as he chose. The reliability of the personality score on one test was .91, and on the other, with only half as many items, .64. Corrected reliabilities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1965
1965
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…For example, the work of Festinger (1942) precisely delineated the positive relationship between difficulty of judgment and judgment time. Later studies, which utilized tasks in which discrete decision delays were associated with the acquisition of specific pieces of information, found information search to be related to the complexity of the problem (or the subject's uncertainty) and to the cost of information (Irwin & Smith, 1956, 1957Lanzetta & Kanareff, 1962) These and other studies (Becker, 1958;Messick & Hills, 1960;Wolff, 1955) found that individuals differ reliably in their proclivities for predecisional search. Thus, more 1 This study is based upon a dissertation presented by the senior author in partial fulfillment of the requirements for the doctor's degree at the University of Delaware, 1963 The study was supported by Grant Number AF-AFOSR-62-9S, United States Air Force, Air Force Office of Scientific Research, Office of Aerospace Research, Washington 25, D. C Thanks are extended to Berj Harootunian and Howard Lamb for their cooperation in arranging the group testing sessions extensive search has been associated w paranoia (Binder, 1958) and with lack confidence (Pruitt, 1957).…”
Section: Goucher College and The University Oj Delawarementioning
confidence: 92%
“…For example, the work of Festinger (1942) precisely delineated the positive relationship between difficulty of judgment and judgment time. Later studies, which utilized tasks in which discrete decision delays were associated with the acquisition of specific pieces of information, found information search to be related to the complexity of the problem (or the subject's uncertainty) and to the cost of information (Irwin & Smith, 1956, 1957Lanzetta & Kanareff, 1962) These and other studies (Becker, 1958;Messick & Hills, 1960;Wolff, 1955) found that individuals differ reliably in their proclivities for predecisional search. Thus, more 1 This study is based upon a dissertation presented by the senior author in partial fulfillment of the requirements for the doctor's degree at the University of Delaware, 1963 The study was supported by Grant Number AF-AFOSR-62-9S, United States Air Force, Air Force Office of Scientific Research, Office of Aerospace Research, Washington 25, D. C Thanks are extended to Berj Harootunian and Howard Lamb for their cooperation in arranging the group testing sessions extensive search has been associated w paranoia (Binder, 1958) and with lack confidence (Pruitt, 1957).…”
Section: Goucher College and The University Oj Delawarementioning
confidence: 92%